Final Design, Manufacturing and Testing of the Clean Sky 2 Distributed Electric Propulsion Scaled Flight Demonstrator D08 DEP-SFD - Doll, C.; Hoogreef, M.; Iannelli, P.; Jentink, H.W.; Kierbel, D. (AIAA, 2024)
Within the work package radical new aircraft configuration of Cleansky2 Large Passenger Aircraft, a benefit of more than 20% in fuel consumption and CO2 emission (one of CS2 top level objectives) could be achieved by using various Distributed (hybrid) Electric Propulsion DEP architectures on different more or less radical aircraft configurations. It has therefore been identified as a disruptive technology which shall be de-risked in terms of achievable performance during wind tunnel tests and in terms of handling qualities during flight tests. The electric architecture with typical magnitudes shall also be studied in more detail. As already presented during AIAA SciTech Forum and Exhibition 2023, the D08 Distributed Electric Propulsion DEP version of the D03 Scaled Flight Demonstrator has been designed, manufactured and ground tested from 2020 to May 2023. An incident during the last ground test in May 2023 caused the total loss of this demonstrator. After its analysis, it was decided to robustify the electric architecture by improving the batteries, the wiring, the protections and the monitoring. These changes in the electric architectures lead to structural changes like the shift of the emergency parachute and bigger access hatches. The remanufacturing of the DEP-SFD2 has started in September 2023 for an exhaustive integration test campaign and taxi tests in January and February 2024. At the moment, the qualification flight tests will take place in April 2024 and the mission flight tests in May 2024.